2018
DOI: 10.5650/jos.ess18131
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase Subtilisin/Kexin Type 9 Is Associated with Degenerating Adipocytes in Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a common disease among the elderly. Recently, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have been indicated as useful therapeutic tools for the treatment of cardiovascular diseases. The aim of this study was to elucidate the role of PCSK9 in the pathogenesis of AAA. We used fluorescence immunohistochemistry to assess the expression of PCSK9 in aortic tissues resected from 24 patients with AAA. Histological examination showed that PCSK9 expression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…It was proposed that decreased PCSK9 in aortic adventitia might upregulate adipocytokine expression in hypertrophic adipocytes through CD36 degradation, thereby contributing to AAA formation. Taken together, these findings suggest that PCSK9 may promote the development of atherosclerosis and upregulate extracellular matrix degradation and adipocytokine expression, thereby contributing to the AAA formation [10]. As shown in the literature, the role of PCSK 9 in the formation of AAA was demonstrated, and thereby it can also be incriminated in our patient, as well.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was proposed that decreased PCSK9 in aortic adventitia might upregulate adipocytokine expression in hypertrophic adipocytes through CD36 degradation, thereby contributing to AAA formation. Taken together, these findings suggest that PCSK9 may promote the development of atherosclerosis and upregulate extracellular matrix degradation and adipocytokine expression, thereby contributing to the AAA formation [10]. As shown in the literature, the role of PCSK 9 in the formation of AAA was demonstrated, and thereby it can also be incriminated in our patient, as well.…”
Section: Discussionsupporting
confidence: 82%
“…Basically, even the ESC guidelines for dyslipidemia management show that, under exclusive statin treatment, the LDL reduction rate is at most 50%. By adding a PCSK9 inhibitor, it increases to at least 75%, implicitly decreasing the risk of CV events [10]. We have preferred the therapeutic combination of atorvastatin 20 mg/day (low dose due to significant hepatic cytolysis at admission) + PCSK9 inhibitor 75 mg SC once every 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that other LDLR‐independent mechanisms might be involved in PCSK9‐induced AAA. Interestingly, the histological examination revealed a significant increase in PCSK9 expression in degenerative media and a decreased PCSK9 and increased CD36 expression in the adventitia region of human aneurysmal samples (Tanaka et al, 2018). It was reported that increased CD36 expression contributes to the accumulation of hypertrophic adipocytes in the aortic adventitia, and hypertrophic adipocytes secrete excessive adipocytokines that are associated with AAA pathogenesis (Doderer et al, 2018; Kugo et al, 2016; Tanaka et al, 2015).…”
Section: Pcsk9 and Vascular Diseasementioning
confidence: 99%
“…It was reported that increased CD36 expression contributes to the accumulation of hypertrophic adipocytes in the aortic adventitia, and hypertrophic adipocytes secrete excessive adipocytokines that are associated with AAA pathogenesis (Doderer et al, 2018; Kugo et al, 2016; Tanaka et al, 2015). Therefore, it was proposed that decreased PCSK9 in aortic adventitia might upregulate adipocytokine expression in hypertrophic adipocytes through CD36 degradation, thereby contributing to AAA formation (Figure 4; Tanaka et al, 2018). Taken together, these findings suggest that PCSK9 may enhance the apoptosis and dedifferentiation of VSMCs, promote the development of atherosclerosis, and upregulate extracellular matrix degradation and adipocytokine expression, thereby contributing to the AAA formation.…”
Section: Pcsk9 and Vascular Diseasementioning
confidence: 99%
“…The association between serum PCSK9 concentrations and the progression of abdominal aortic aneurysm also presented a clinical translation since the increased PCSK9 concentrations could reduce the hepatic LDL receptor (LDLR), resultantly causing the higher LDL-C and further promoted the progression of hyperlipidemia [46,47]. Furthermore, the inflammatory response and dyslipidemia were correlated due to the risk of dyslipidemic related cardio-metabolic diseases could be also induced by lowgrade inflammatory response via the stimulation of the NLRP3 inflammasome and other pro-inflammatory signaling pathways [48,49].…”
Section: Mechanic Linkage Between the Risk Of Dyslipidemia With Bavmentioning
confidence: 99%